Perovskite-metal-oxide-based advanced oxidation technology for water treatment application - Leiw, Ming Yian (2014)
Advanced oxidation processes (AOPs) currently used for water treatment are usually chemical and energetical intensive processes. In this project, Strontium Ferrite (SFO) was explored as an alternative material for bifunctional AOP for cost-effective water treatment application. The perovskite SFO metal oxide particles were prepared by a combined high temperature and high-energy ball milling process and their physicochemical properties were characterized systematically. The SFO could breakdown toxic and carcinogenic pollutants such as BPA and AO8 under dark ambient condition. Intermediate byproducts and responsible reactive oxidative species were identified to understand the dark oxidative degradation mechanism. Degradation efficiencies were enhanced under visible light illumination. However, the SFO was partially decomposed into strontium carbonate due to carbon dioxide poisoning. Substitution of iron atoms by titanium atoms, forming solid solutions STFx metal oxides could improve the structural stability of the SFO but at the expense of oxidative degradation performance with increasing titanium composition.